Faktor-Faktor yang Mempengaruhi Profitabilitas pada Bank Umum Konvensional di Indonesia Tahun 2020-2024 - Ananda, Savira; Armeliza, Diah; Handarini, Dwi (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2025)
This study aims to analyze the factors influencing the profitability of conventional commercial banks in Indonesia. The study used secondary data in the form of financial statements of conventional commercial banks for the 2020–2024 period, selected using a purposive sampling method. Data analysis was performed using panel data regression with the help of Microsoft Excel and EViews 13 software. The results showed that Net Interest Margin (NIM) and Total Asset Turnover (TATO) had a positive and significant effect on profitability (ROA). Conversely, the Capital Adequacy Ratio (CAR), Operating Costs to Operating Income (BOPO), and Non-Performing Loans (NPL) had a negative and significant effect on profitability (ROA). Meanwhile, the Loan to Deposit Ratio (LDR) did not have a significant effect on profitability. These findings confirm that bank profitability is more determined by the effectiveness of interest income management, asset utilization efficiency, and control of operational costs and credit risk, rather than the level of credit distribution. The results of this study are expected to serve as a reference for banking management and the development of empirical studies in the fields of financial accounting and banking.